Healthy Pacific grandparents: a participatory action research project exploring ageing well among Pacific people in New Zealand. (3rd April 2017) - Tautolo, El-Shadan; Wrapson, Wendy; Paterson, Janis; Clair, Valerie Wright-St; Neville, Stephen; Dewes, Ofa; Iusitini, Leon
ABSTRACT: The New Zealand older adult population (aged 65+ years) is growing at a faster rate than the younger population, with many of those in the later years living much longer. The proportion of older Pacific people is forecast to reach 4.1% of the country's total population within the next two decades, highlighting the importance of research focused on ageing Pacific populations. This article sets out the research protocol and methods for the Pacific Islands Families: Healthy Pacific Grandparents' Study, which aims to investigate older Pacific people's viewpoints on ageing to identify specific cultural values, perspectives and understandings as the Pacific population in New Zealand ages. The study will recruit and utilize participants from a grandparent cohort that is nested within the families of the longitudinal Pacific Islands Families Study. This study uses a Participatory Action Research approach to position the participants in a leadership role where they are co-researchers involved in both the research and the implementation of recommendations. Utilizing a transformative research process will bring older Pacific people together to define for themselves their needs and their experiences, identify any areas of shortcoming, and support the implementation of solutions through strategic and informed actions.